1990
DOI: 10.1007/bf02718151
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between outdoor NO2 and respiratory symptoms in preschool children

Abstract: A study of 1225 preschool children was conducted in four regions of Switzerland with different levels of air pollution to investigate the relationship between air pollution and respiratory symptoms. Daily symptoms were recorded by parents on a diary form and air pollution exposure assessed by personal NO2 samplers. Each family participated for 6 weeks and personal samplers were changed every week. The frequency of respiratory symptoms per child and day was found to increase with increasing levels of NO2 measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…m -3 ) outdoors and the incidence of respiratory symptoms among Swiss children aged 0±5 yrs. RUTISHAUSER et al [11] found, in the same age group of Swiss children, a Table 3. ± The seasonal prevalence rates (i.e., the proportion of the number of days with symptoms to the number of follow-up days per person) of cough and nasal symptoms in different categories of weekly average NO 2 ) and the respiratory symptoms.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…m -3 ) outdoors and the incidence of respiratory symptoms among Swiss children aged 0±5 yrs. RUTISHAUSER et al [11] found, in the same age group of Swiss children, a Table 3. ± The seasonal prevalence rates (i.e., the proportion of the number of days with symptoms to the number of follow-up days per person) of cough and nasal symptoms in different categories of weekly average NO 2 ) and the respiratory symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…Outdoor exposure estimates have usually been based on fixed-site monitoring data or on diffusion sampler measurements outside the home. In two previous studies, in which personal monitoring of the total NO 2 exposure has been used, SAMET et al [8] did not find a significant association between exposure and respiratory illness among children aged <18 months, whereas RUTISHAUSER et al [11] found an increased frequency of respiratory symptoms with increasing NO 2 exposure among children <5 yrs of age.…”
mentioning
confidence: 96%
“…When atopic and nonatopic patients were handled separately, the association with air pollution was unaffected (31,33,34). This suggests that both asthma subpopulations are affected equally by air pollution.…”
Section: Introduction Urban Air Toxicsmentioning
confidence: 97%
“…5 In Brazil, time-series studies have assessed the impact of pollutants on population health. 8,17,18 A study performed in the two largest Brazilian cities, Rio de Janeiro and São Paulo, 8 found that air pollution was associated with both respiratory and cardiovascular health. The number of hospitalizations due to respiratory diseases in children rose as a result of increases in pollution: 1.8% in Rio de Janeiro and 6.7% in São Paulo for 10μg/m 3 increases in PM10 (particulate material with up to 10 micrometers in diameter); yet in São Paulo, 6.7% for 10μg/m 3 increases in SO 2 (sulfur dioxide) and 1.7% for 1ppm increases in CO (carbon monoxide).…”
Section: Introductionmentioning
confidence: 99%